2021
DOI: 10.3390/fluids6040155
|View full text |Cite
|
Sign up to set email alerts
|

Jet Dynamics Associated with Drop Impact on Micropillared Substrate

Abstract: The jetting phenomenon associated with droplet impact upon a hydrophilic micropillared substrate was analyzed in detail using a high-speed camera. Viscosities of the fluids were varied using differing concentrations of glycerol in deionized water. This paper aims to connect similarities between this form of capillary jetting and another well-known jetting phenomenon from the bubble bursting. Both experience a cavity collapse when opposing fluid fronts collide which causes a singularity at the liquid surface, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…in such a way that daughter droplets are produced from a microliter-sized droplet. Impacting the droplet at a higher Weber number, We > 46, could result in the jetting of the droplet on retraction and breakage of the liquid column to emit a single satellite droplet. ,,, Sprittles et al demonstrated the formation of large spherical liquid marbles along with uncoated satellite droplets at We = 46 . They observed the production of multiple satellite droplets at a higher We (>52), but not all resulted in the formation of completely covered marbles.…”
Section: Introductionmentioning
confidence: 99%
“…in such a way that daughter droplets are produced from a microliter-sized droplet. Impacting the droplet at a higher Weber number, We > 46, could result in the jetting of the droplet on retraction and breakage of the liquid column to emit a single satellite droplet. ,,, Sprittles et al demonstrated the formation of large spherical liquid marbles along with uncoated satellite droplets at We = 46 . They observed the production of multiple satellite droplets at a higher We (>52), but not all resulted in the formation of completely covered marbles.…”
Section: Introductionmentioning
confidence: 99%
“…These jetting events are often accompanied by the capillary end-pinching of the jet as it reaches the maximum height and the subsequent release of the secondary droplet(s). Siddique et al and Asai et al showed that for the impact of viscous droplets (viscosity higher than DI-water) on a micropatterned hydrophilic surface, the jet velocity ( U j ) and the top secondary droplet size ( d j ) religiously follows the scaling law of Gañán-Calvo, i.e., γ ρ d j η 2 ( η U j γ ) 5 / 3 . Here, the variables ρ, γ, and η denote the experimental fluids’ density, surface tension, and dynamic viscosity, respectively.…”
Section: Introductionmentioning
confidence: 99%